Plant Nematology - Perry, Ronald N.; Moens, Maurice (Oxfordshire: CABI, 2006)
this book provides an indispensible overview of all aspects of plant-parasitic nematodes. It begins by reviewing the basic structure and classification of nematodes, their taxonomy and phylogeny and the major groups of plant-parasitic nematodes. It moves on to cover their life cycle biology, the molecular characteristics of plant-nematode interaction and genetic engineering for resistance. The final section discusses quarantine legislation, sampling methods and management strategies including cultural schemes, the use of chemicals and resistant cultivars.
Bibliography 411-431p.; Glossary 432-439p.; Index 440-447p.
Keywords: Nematode diseases of plant; Nematology; Taxonomy; General Science